BAF53/Arp4 Homolog Alp5 in Fission Yeast Is Required for Histone H4 Acetylation, Kinetochore-Spindle Attachment, and Gene Silencing at Centromere - Minoda, Aki (The American Society for Cell Biology, 2005)
Nuclear actin-related proteins play vital roles in transcriptional regulation; however, their biological roles remain elusive. Here, we characterize Alp5, fission yeast homolog of Arp4/BAF53. The temperature-sensitive mutant alp5-1134 contains a single amino acid substitution in the conserved C-terminal domain (S402N) and displays mitotic phenotypes, including chromosome condensation and missegregation. Alp5 forms a complex with Mst1-HAT (histone acetyltransferase). Consistently, inhibition of histone deacetylases (HDACs), by either addition of a specific inhibitor or a mutation in HDAC-encoding clr6(+) gene, rescues alp5-1134. Immunoblotting with specific antibodies against acetylated histones shows that Alp5 is required for histone H4 acetylation at lysines 5, 8, and 12, but not histone H3 lysines 9 or 14, and furthermore Clr6 plays an opposing role. Mitotic arrest is ascribable to activation of the Mad2/Bub1 spindle checkpoint, in which both proteins localize to the mitotic kinetochores in alp5-1134. Intriguingly, alp5-1134 displays transcriptional desilencing at the core centromere without altering the overall chromatin structure, which also is suppressed by a simultaneous mutation in clr6(+). This result shows that Alp5 is essential for histone H4 acetylation, and its crucial role lies in the establishment of bipolar attachment of the kinetochore to the spindle and transcriptional silencing at the centromere.